A study of the correlation between sarcopenia and cognitive impairment in older individuals over 60 years: cross-sectional and longitudinal validation - Dong, Xiaohan; Yu, Yichao; Li, Jiahao; Chai, Xinyu; Shan, Wei; Yan, Huiping; Lu, Yifan (Frontiers in Aging Neuroscience, 2024)
ObjectiveTo validate the correlation between sarcopenia and cognition, and explore cognitive subdomains affected by sarcopenia.MethodsA case–control study was designed to recruit 90 individuals aged 60 and above from June to October 2023 in the same community, all individuals meeting the inclusion criteria were categorized according to the 2019 Asian criteria for sarcopenia and divided into the sarcopenia group and non-sarcopenia group at baseline. After a 12-week follow-up recording, individuals were classified into the aggravation group and alleviation group based on the change of sarcopenia severity. Sarcopenia tests including muscle mass, calf circumference, grip strength and physical function assessment, using Montreal Cognitive Assessment (MoCA) of nine dimensions for cognitive assessment.Results(1) There was a significant positive correlation between cognitive function and grip strength in males (r = 0.42, p < 0.05). (2) There was a moderate correlation between sarcopenia grading and MoCA score (r = −0.4, p < 0.001). (3) Individuals with sarcopenia had significantly lower MoCA total scores and sub-scores in executive function, fluency, calculation and delayed recall compared to non-sarcopenia group (p < 0.05). (4) After 12 weeks, the mean value of the change in fluency in the alleviation group increased by 0.33 points, while the aggravation group decreased by 0.2 points (W = 128, p < 0.05).ConclusionThere is a correlation between sarcopenia and cognitive function, individuals with sarcopenia performing poorly in overall cognition as well as refined dimensions. The degree of cognition like fluency degenerates over time with increasing severity of sarcopenia.